Penerapan Model Pembelajaran Menyimak Tipe Bisik Berantai Mata Pelajaran Bahasa Indonesia Pada Siswa Kelas III SDN Milangsari 2 Kecamatan Panekan Kabupaten Magetan - Suparti Suparti; V. Teguh Suharto; Sigit Ricahyono (Universitas PGRI Madiun, 2023)
This research is descriptive qualitative aims to reveal facts, circumstances, phenomena, variables, and circumstances regarding the learning model of listening to whispers in a chain. Descriptive qualitative research interprets and tells data related to the current situation, attitudes and views that occur in society, the contradiction of two or more circumstances, the relationship between variables, differences between facts, the influence of a condition and others. The results of research related to the problems that exist in the application of listening to the type of whisper chain are: 1. The application of the learning model of listening to whispers in a chain, to the lesson plans in accordance with scientific principles, which include, among others, in the implementation based on the results of observations: the results obtained (a) the teacher in delivering the introduction in learning obtained a % score of 96.00% with a very good category; (b) the core activities carried out in learning to listen to the type of whispering chain obtained a score of 96% with a very good category; (c) in closing the learning, the results obtained are 92% in the very good category, and (d) overall in learning activities, the total score is 92.67%, with a very good classification. 2. Cognitive Learning Outcomes: Cognitive assessment of the results if the KKM is determined as 75, this means that there are 3 students who have not completed their studies or 16.67%, (acquisition value < KKM or KBM), and 15 students or 83 students who have completed their studies. ,33% (scoring > KKM or KBM. 3. The problems encountered in learning to listen: One of the shortcomings of the results of this study are (a) students still do not perceive the whisper-chained listening learning model as a need to organize learning, (b) the lack of student experience in using chain-whisper learning models; (c). In a chain whisper, they cannot ask the words to be repeated (d) Students are not easy to concentrate on the words that are whispered to them.